Interlocução entre letramento acadêmico e letramento digital: os efeitos das novas tecnologias nos hábitos de leitura e escrita - Carvalho, Guido de Oliveira (2019)
This research aims at verifying how the course of Letras of UEG-Campus Cora Coralina is performing the academic reading and writing activities, particularly in the production of academic discursive/textual genres, in face of the development of Information and Communication Technologies (ICT), thus contributing to discussions on academic and digital literacy. To carry out the research, we used qualitative approach procedures, in order to analyze the research object and seek to understand it in its totality in a reflective process. The type of research is the case study, which seeks to examine a phenomenon in its real context, in our research one of the Letras courses at UEG, so the context of our research focuses on the university environment. The data collection, conducted in 2018, used three instruments: documents from Letras Course UEG-Campus Cora Coralina (Political Pedagogical Project, Regulation of Term Paper; Regulation of Internship, Resolution of Complementary Activities and academic subjects’ programs); questionnaires and interviews applied to students and teachers. For our discussion, we sought theoretical support in New Literacy Studies (NEL), which focuses on reading and writing practices in social and cultural contexts (LEA; STREET, 1998, 2014; STREET, 2014; GEE, 2015). We have also mobilized the theoretical framework of Academic Literacy (FISCHER, 2007, 2008; MARINHO, 2010; FIAD, 2011; LEA; STREET, 2014; STEPHANI; ALVES, 2017, among others) and digital literacy (SOARES, 2002; XAVIER, 2007; GAMA, 2012; THEISEN, 2015; DUDENEY, HOCKLY; PEGRUM, 2016, among others). The discussion about academic discursive/textual genres is based on Bakhtin (2003), Sobral (2009), Marcuschi (2008, 2010), Souza and Bassetto (2014), Rojo and Barbosa (2015), Fiorin (2017), among others. We conclude from the data that the course documents align with the university's usual tripod: teaching, research and extension programs, highlighting its role as a knowledge producer through the production of term paper or participation in academic programs such as PBIC, PIBIC or Pibid, which represents a practice of academic literacy. The analysis of the questionnaires and interviews reveals that if, on the one hand, the documents provide few actions that lead to digital literacy, on the other hand, students and teachers have access to ICT, use them in their daily life and for their academic purposes, being digital literates, at least as necessary for their participation in the academy. We designate the moments when academic practices meet digital practices as “digital-academic literacy events”. Finally, whether on the computer, mobile phone or tablet, academy members are reading and writing the required academic genres in the course in question, as well as using the internet to establish teacherstudent-student communication and access to academic practices.